2015
DOI: 10.1016/j.virol.2014.11.021
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of a polyomavirus microRNA highly expressed in tumors

Abstract: Polyomaviruses (PyVs) are associated with tumors including Merkel cell carcinoma (MCC). Several PyVs encode microRNAs (miRNAs) but to date no abundant PyV miRNAs have been reported in tumors. To better understand the function of the Merkel cell PyV (MCPyV) miRNA, we examined phylogenetically-related viruses for miRNA expression. We show that two primate PyVs and the more distantly-related raccoon PyV (RacPyV) encode miRNAs that share genomic position and partial sequence identity with MCPyV miRNAs. Unlike MCPy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 75 publications
(101 reference statements)
2
37
0
Order By: Relevance
“…[45][46][47][48][49][50][51][52][53][54][55][56] Therefore, the decoy cell cytomorphologic template may be relevant for both BK and JC polyomavirocytes arising from any locus throughout the urinary tract. Unlike surgical biopsy, voided urine cytopathology may sample the entire urinary tract and because of this expanded degree of representation may prove sensitive in revealing PyV involvement through the detection of urinary decoy cells.…”
Section: Decoy Cell Cytomorphology Backgroundmentioning
confidence: 99%
“…[45][46][47][48][49][50][51][52][53][54][55][56] Therefore, the decoy cell cytomorphologic template may be relevant for both BK and JC polyomavirocytes arising from any locus throughout the urinary tract. Unlike surgical biopsy, voided urine cytopathology may sample the entire urinary tract and because of this expanded degree of representation may prove sensitive in revealing PyV involvement through the detection of urinary decoy cells.…”
Section: Decoy Cell Cytomorphology Backgroundmentioning
confidence: 99%
“…Mittledorf and colleagues (2012) [17] reported HPV6 and MCPyV DNA in a combined MCCinvasive SCC. Furthermore, two recent studies have already demonstrated MCPyV DNA in 19 to 37% cervical carcinomas, and one study reported a combined MCC-SCC involving HPV-MCPyV detection in the vulva [18] suggesting that MCPyV might play a role as cofactor to HPV-related cancers [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…However, some specialized algorithms have been developed to identify specific types of ncRNAs. Perhaps the most successful examples are algorithms to identify transfer RNA (tRNA) genes [24][25][26][27][28]. Eukaryotic tRNAs, 7SL RNA, Alu SINEs, adenovirus VA RNAs, and the murine gammaherpesvirus 68 microRNAs (miRNAs) all share a similar RNA Polymerase III (RNAP III) type 2 gene structure.…”
Section: Prediction Algorithmmentioning
confidence: 99%
“…If abundant RNA from infected cells/tissues is not available, the predicted gene (the RNAP III transcription elements/predicted RNA product plus flanking sequence) can be synthesized commercially and cloned into plasmid expression vectors [19,21,26]. These vectors are then transfected into HEK293T cells and analyzed via sequencing [19,21,27] and/or Northern blot as previously described in detail [28], to determine if the DNA of interest expresses a small RNA. Next generation sequencing (currently we use the Illumina platform) of small RNAs should reveal reads consistent with a specifically processed (well-defined 5' and 3' termini) abundant small RNA, the miRNA, and typically a less abundant miRNA mapping to the other arm of the pre-miRNA hairpin.…”
Section: Validation Of Rnap Iii-dependent Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation